DNA isolation from whole blood using in-house method versus commercialized techniques: quality and cost consideration - A.Talib, Norlelawati; Mohammad, Salina; Abdullah, Nor Zamzila; F.W, Mustafa Fadzil (College of Pathologists, Academy of Medicine Malaysia, 2010)
Background: Isolation of deoxyribonucleic acid (DNA) from whole blood is among the crucial steps prior to molecular diagnostic or research in human genetics. As the isolation techniques have progressively evolved, the manual techniques for DNA purifi cation have been gradually replaced by automation and purifi cation kits. Though expensive, these techniques were preferred due to their superiority in extracting DNA from small volume of sample and their safer and rapid procedure. Objective: The purpose of this study is to compare the cost and quality of DNA purifi cation between manual technique and the commercialized techniques. Method: Manual salting out procedure technique was adopted and optimized to purify DNA from small volume of blood. The quality and quantity of DNA were compared to two commercialized techniques, QIAmp DNA extraction kit (Qiagen) and fully automated technique (Magtration 12C, Precision). The costs per extraction were calculated based on the actual cost incurred for the procurement of all reagents, chemicals and kits used in this study. Result: Apart from being a relatively safe and cheap technique, we found that the optimized salting-out procedure was able to extract comparable quantity and quality of DNA from small volume of blood. Conclusion: The main advantage of in house DNA purifi cation method was its minimum costs. The method is also suitable in laboratory with good human resource but limited fi nancial support.